Prophetic Leadership in Islamic Educational Institutions in the 4.0 Era - Ghazali, Ziyadul Ifdhal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
In the industrial era 4.0, the major crisis faced by Islamic educational institutions is the exemplary crisis. Exemplary is closely related to leadership which is also one of the important and even crucial factors in an educational institution. Leadership is a source of aspirational power that can trigger the growth of spirit, morality and creativity of every stakeholder involved to work together and collaborate so that the vision, mission and goals of educational institutions can be realized effectively. In the context of Islamic educational institutions, leadership has complex dimensions. Leaders in Islamic education are not only required to have managerial skills but are also required to have the ability to instill Islamic religious values within the organization. Prophetic leadership so far is believed to be the ideal conception of leadership in Islamic educational institutions, apart from being sourced from Islamic religious values, prophetic leadership also has a rule model that can be used as an example as well as a role model so that the conception of prophetic leadership is not a utopian one. It is hoped that through prophetic leadership it can raise the enthusiasm and performance of Islamic educational institutions so that the ideals of Islamic education in this millennial era can be realized.